2010
DOI: 10.1093/humrep/deq044
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of dietary fat consumption and endometriosis risk

Abstract: These data suggest that specific types of dietary fat are associated with the incidence of laparoscopically confirmed endometriosis, and that these relations may indicate modifiable risk. This evidence additionally provides another disease association that supports efforts to remove trans fat from hydrogenated oils from the food supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
169
2
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(197 citation statements)
references
References 24 publications
7
169
2
19
Order By: Relevance
“…Three types of endometriosis have been described, including peritoneal, ovarian, and deep infiltrating endometriosis [4]. Immune, endocrine, genetic, and anatomical disorders have been mentioned as risk factors [5,6], but the etiology of the disease is not fully understood [7].…”
Section: Introductionmentioning
confidence: 99%
“…Three types of endometriosis have been described, including peritoneal, ovarian, and deep infiltrating endometriosis [4]. Immune, endocrine, genetic, and anatomical disorders have been mentioned as risk factors [5,6], but the etiology of the disease is not fully understood [7].…”
Section: Introductionmentioning
confidence: 99%
“…In another study done by Missmer and colleagues (2010), it was demonstrated that women using omega-3 develop endometriosis 22% less, and consumers of trans, unsaturated fatty acids 48% more (20).…”
Section: Discussionmentioning
confidence: 98%
“…Более низкий показатель заболеваемости эндо-метриозом наблюдается у пациенток, в анамнезе ко-торых были многократные роды, длительное корм-ление грудью [8].…”
unclassified
“…Диетическое питание с повышенным по-треблением свежих фруктов, зеленых овощей, содер-жащих омега-3 жирные кислоты, снижает вероят-ность развития эндометриоза [8].…”
unclassified
See 1 more Smart Citation